Sustainable public procurement for a sustainable food system: An exploratory study of Portuguese public schools - Bizarro, Sofia; Ferreiro, Maria de Fátima; Salavisa, I. (Royal Geography Society-IBG Annual International Conference 2021, 2021)
The increasing unsustainability generated by the prevailing food system demonstrates the need and opportunity to explore the transformative potential of public procurement as an innovation policy instrument able to foster the transition towards a sustainable future. Particularly regarding the school canteens offer, the criticisms over quality in public sector catering (i.e. OGM foods, frozen meals) and the concerns about health effects (i.e. malnutrition, childhood obesity) boosted a debate around the standards, the food provenance and the rules of acquisition used (Morgan & Sonnino, 2008). Recently, in Portugal, new experiments and organizational models of food governance emerged to challenge this paradigm. Local, municipal and national institutions, driven by regulatory frameworks and the directives of green public procurement, are using its ‘power of purchase’ to promote a broader approach to this multidimensional issue and achieve multiple societal benefits (European Union, 2018). In this context, the present investigation - developed in the research project on Spatial Planning for Change (SPLACH) – focuses on the analysis of innovative procedures of public procurement in Portuguese schools. This study aims to understand the attributes and the criteria required in public contracts of acquisition of goods and services, namely the specifications about environmental conditions, local chains and quality patterns (freshness, nutritional value, seasonality or organic products). The analysis aims to provide a short overview of the evolution of European and national regulatory instruments, examining the barriers and the new opportunities created in school food provisioning for local food procurement and the re-localization of the food chain.